THE INFLUENCE OF ESG PERFORMANCE, PROFITABILITY AND CAPITAL INTENSITY ON TAX AVOIDANCE: case study of manufacturing in consumer goods on the Indonesia Stock Exchange for the 2021-2024 period) - Intan Permata Sari (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
Tax avoidance is a form of minimizing and reducing the tax burden through actions that are not prohibited by law. Tax avoidance is part of tax planning, unlike tax evasion, which is clearly prohibited by law. Tax avoidance is carried out by exploiting legal loopholes such as transfer pricing or transferring profits from a region with a high tax rate to the same company in a region with a low tax rate. Although this is legal, it can have a negative impact in the form of decreased tax revenue. This study aims to determine the effect of ESG performance, profitability, and capital intensity on tax avoidance in consumer goods sub-sector manufacturing companies listed on the Indonesia Stock Exchange with a research period of 2021-2024. This study is a quantitative study with a purposive sampling method obtained 24 companies with a sample size of 78 data and using multiple linear regression analysis tests and the data were processed using SPSS. The results obtained are: ESG performance has no effect on tax avoidance, profitability does not affect tax avoidance, capital intensity has a positive effect on tax avoidance, and overall ESG performance, profitability, and capital intensity have a significant effect on tax avoidance.